2014
DOI: 10.1063/1.4865318
|View full text |Cite
|
Sign up to set email alerts
|

Composition and crystallinity in electrochemically deposited magnetostrictive galfenol (FeGa)

Abstract: Articles you may be interested inElectrodeposition and characterization of magnetostrictive galfenol (FeGa) thin films for use in microelectromechanical systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…5b summarizes the dependence of Ga concentration on rotation rate, deposition potential, and electrolyte concentration. This bar chart shows that the composition can be controlled over the 15%Ga to 35%Ga range that has been shown to have useful magnetostriction constants [15]. It is also important to note that the Fe 1−x Ga x films made within the parameters studied here did not contain oxygen impurities within the limit of detection.…”
Section: B Film Compositionmentioning
confidence: 75%
See 1 more Smart Citation
“…5b summarizes the dependence of Ga concentration on rotation rate, deposition potential, and electrolyte concentration. This bar chart shows that the composition can be controlled over the 15%Ga to 35%Ga range that has been shown to have useful magnetostriction constants [15]. It is also important to note that the Fe 1−x Ga x films made within the parameters studied here did not contain oxygen impurities within the limit of detection.…”
Section: B Film Compositionmentioning
confidence: 75%
“…McGary and then later refined and characterized by Reddy and Estrine [15], [20]- [22]. In these works, uniform, high quality films were deposited onto rotating disk electrodes (RDE), and the importance of boundary layer control was shown.…”
Section: Electrodeposition Of Fe 1−x Ga X Was First Demonstrated Bymentioning
confidence: 99%
“…Estrine showed that sputter-deposited Cr/Cu adhesion layers were effective contacts for the deposition of Galfenol films (170 nm) onto glass coverslips [16]. Magnetostriction was measured as high as 140 ppm for these 17–21% Ga films.…”
Section: Galfenol Films and Propertiesmentioning
confidence: 99%
“…In recent years, magnetostriction properties of rare-earth-transition metal films have attracted much interest in sensitive, low-power spintronic devices and other magnetostriction microdevices [1][2][3][4][5][6][7][8][9][10][11][12]. Among giant magnetostrictive materials, FeGa is well known because of its low cost and easy manufacturing process [13][14][15]. Although FeGa has a high magnetostriction performance, the effective magnetostriction coefficient (λ eff ) of asdeposited FeGa film is less than 100 ppm [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Among giant magnetostrictive materials, FeGa is well known because of its low cost and easy manufacturing process [13][14][15]. Although FeGa has a high magnetostriction performance, the effective magnetostriction coefficient (λ eff ) of asdeposited FeGa film is less than 100 ppm [15,16]. In contrast, thin films of rare-earth-transition metal alloys, such as TbFe-based alloys, which have enormous magnetostrictive performance, are considered to be promising materials for magnetostrictive devices.…”
Section: Introductionmentioning
confidence: 99%